Acetylation of proximal cysteine-lysine pairs by alcohol metabolism - Courtney D. McGinnis; Peter S. Harris; Brenton I.M. Graham; John O. Marentette; Cole R. Michel; Laura M. Saba; Richard Reisdorph; James R. Roede; Kristofer S. Fritz (Redox Biology)
Alcohol consumption induces hepatocyte damage through complex processes involving oxidative stress and disrupted metabolism. These factors alter proteomic and epigenetic marks, including alcohol-induced protein acetylation, which is a key post-translational modification (PTM) that regulates hepatic metabolism and is associated with the pathogenesis of alcohol-associated liver disease (ALD). Recent evidence suggests lysine acetylation occurs when a proximal cysteine residue is within ∼15 Å of a lysine residue, referred to as a cysteine-lysine (Cys-Lys) pair. Here, acetylation can occur through the transfer of an acetyl moiety via an S → N transfer reaction. Alcohol-mediated redox stress is known to occur coincidentally with lysine acetylation, yet the biochemical mechanisms related to cysteine and lysine crosstalk within ALD remain unexplored. A murine model of ALD was employed to quantify hepatic cysteine redox changes and lysine acetylation, revealing that alcohol metabolism significantly reduced the cysteine thiol proteome and increased protein acetylation. Interrogating both cysteine redox and lysine acetylation datasets, 1280 protein structures generated by AlphaFold2 represented by a 3D spatial matrix were used to quantify the distances between 557,815 cysteine and lysine residues. Our analysis revealed that alcohol metabolism induces redox changes and acetylation selectively on proximal Cys-Lys pairs with an odds ratio of 1.88 (p < 0.0001). Key Cys-Lys redox signaling hubs were impacted in metabolic pathways associated with ALD, including lipid metabolism and the electron transport chain. Proximal Cys-Lys pairs exist as sets with four major motifs represented by the number of Cys and Lys residues that are pairing (Cys1:Lys1, Cysx:Lys1, Cys1:Lysx and Cysx:Lysx) each with a unique microenvironment. The motifs are composed of functionally relevant Cys-Ly altered within ALD, identifying potential therapeutic targets. Furthermore, these unique Cys-Lys redox signatures are translationally relevant as revealed by orthologous comparison with severe alcohol-associated hepatitis (SAH) explants, revealing numerous pathogenic thiol redox signals in these patients.